Pripoved in dogodek - Snoj, Vid (Primerjalna književnost, 2009)
This article discusses narrative in historiography and literary historiography, which was called into question by the metacritical reflection of both disciplines. It advocates the existence of narrative in these disciplines and bases the literary-historical narrative on the literary event.
Keywords: history of literature; literarna zgodovina; history; zgodovinopisje; literature; književnost; pripoved; zgodba; dogodek; esencializem; relacionizem; Longin; vzvišeno; das Unheimliche